(untitled) (Research, Society and Development, 2022)
The water resource is one of the main limiting factors for crop productivity. Poor distribution of rainfall is a serious problem in rainfed agriculture. The occurrence of periods of water deficit in the soil in the most sensitive phases of the crop can result in significant losses in productivity and in the use of nutrients. The use of Superabsorbent Polymers can be a strategy to minimize the risks of planting under water deficit conditions. Thus, the objective was to determine physiological responses and production components of common bean (Phaseolus vulgaris) in response to phosphate fertilization combined with doses of polymers in the presence or absence of water deficiency in the soil. The experiment was set up in a greenhouse in 150 dm3 pots with 17 bean plants in each pot. The treatments consisted of three factors that were combined in a factorial scheme: two water regimes (with and without water deficit), two doses of P (ideal and 1/3 ideal) and five doses of polymers (0, 2, 4, 8, 16% equivalent of the mass of the phosphate fertilizer for that of 120 kg ha-1 of P2O5). Dry matter was increased by 0.9% at the lowest dose of P mixed with 16% of polymer without water deficit and by 0,5% at the highest dose of P mixed with 5% of polymer without water deficit. P accumulation was increased by 16 and 19% at the highest and lowest dose of P mixed with 8,6 and 16% non-water deficit polymer, respectively. The photosynthetic rate and stomatal conductance were lower when the plants were subjected to water deficit. The concentration of proline in the leaf was higher at the lowest dose of P mixed with 8% polymer with and without water deficit, respectively. The number of pods per plant increased by 21 and 6% at the highest and lowest doses of P mixed with 8,9 and 5.46% of polymer without water deficit, respectively. The weight of one hundred grains showed a difference of 0,5% in the highest and lowest doses of P mixed with 2,41 and 16% of polymer without water deficit. Grain yield per pot was increased by 22 and 24% at the highest and lowest dose of P mixed with 13,7 and 16% of polymers without water deficit, respectively. The EUA increased by 21 and 24% at the highest and lowest dose of P mixed with 5,89 and 6,81% of polymer without water deficit, respectively. Superabsorbent polymers can be an alternative to prolong soil moisture and increase the efficiency of phosphate fertilizer.